1961ネン ノ エットウ カンソク カラ ミタ ショウワ キチ ニオケル デンリソウ キョクコウ オヨビ チジキ ヘンカ ノ ソウゴ カンケイ - 川尻, 矗大; カワジリ, ノブヒロ; 若井, 登; ワカイ, ノボル; 中村, 純二; ナカムラ, ジュンジ; 中村, 強; ナカムラ, ツヨシ; 長谷川, 貞雄; ハセガワ, サダオ; KAWAJIRI, Nobuhiro; WAKAI, Noboru; et al. (国立極地研究所, 1965)
P(論文) Ionospheric, auroral and geomagnetic observations were made simultaneously at Syowa Station during the fifth wintering of the Japanese Antarctic Research Expedition in 1961 The ionospheric soundings at vertical incidence were carried out every fifteen minutes. Auroras were measured by photometric technique for the three lines, λ5577A (OI (S-D) line), λ6300A (OI (D-P) line and λ4278A (N G of N_2^+ (0-1) band), and the magnetogram from which the magnetic Qindices were reduced, was obtained by a magnetometer of pen-recording type Based on these data obtained during the winter months, the expressions for the relation between auroral luminosity (J in kR) and electron density (N in electrons/cm^3) in the E region were calculated in the following two ways. 1) When the exponent b of maximum electron density in the expression J=aN^b_<max> is calculated by the method of least squares, it is about 1 6 for λ5577A line and about 1 3 for λ4278A band for the case of E_n (night E layer) or E_<sr> (retadation type of E_s). 2) In case it is assumed beforehand that the auroral luminosity is proportional to the square of maximum electron density in the E-region, the expression becomes J (4278)=1 2×10^<-11>N^2_<max> for the case of the correlation of the 4278 band with E_<sr> layers. In general, type of the sporadic E layer seems to change in the order from E_n to E_<sr>, E_<sa> (auroral type of E_s) and E_<sf> (flat type of E_s, as the geomagnetic disturbance of negative bay type progresses There is a kind of the sporadic E layer which is not accompanied by auroral and geomagnetic disturbances Such E_s layers are apt to take a shape of flat type, and may be, so to speak, of mid-latitudinal type The relations between auroral intensities of λ5577A line and λ6300A line and between auroral luminosity and geomagnetic variation of H component are also discussed departmental bulletin paper